2021
DOI: 10.1017/s1368980021001555
|View full text |Cite
|
Sign up to set email alerts
|

Commercial foods for infants under the age of 36 months: an assessment of the availability and nutrient profile of ultra-processed foods

Abstract: Objective: Considering the negative impact of the consumption of ultra-processed foods on health, this study assessed the availability and nutritional profile of commercial ultra-processed foods for infants in Natal, Brazil. Design: A cross-sectional exploratory study. Setting: Foods targeted at children under the age of 36 months sold in retail establishments located in high and low-income areas of the one capital city of Brazil. Participants: 1,645 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 21 publications
1
16
1
Order By: Relevance
“…Da Rocha et al found in their study that 79% of the baby foods were UP foods. The difference observed compared with our results (61.8%, n = 118) might be explained by the fact their study considered infant and follow-up formulas (n = 31, 33%), and our analysis included the food category fruit purée with cereals/milk, which had 15.8% (n = 29) of foods classified as UP due to the presence of additives in the ingredient list or the manufactured process [16].…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…Da Rocha et al found in their study that 79% of the baby foods were UP foods. The difference observed compared with our results (61.8%, n = 118) might be explained by the fact their study considered infant and follow-up formulas (n = 31, 33%), and our analysis included the food category fruit purée with cereals/milk, which had 15.8% (n = 29) of foods classified as UP due to the presence of additives in the ingredient list or the manufactured process [16].…”
Section: Discussioncontrasting
confidence: 88%
“…For the classification of UP products, the use of industrial techniques, such as extrusion, hydrogenation, and carbohydrate modifications, and the ingredient list was taken into account. Food products where the ingredient list contained additives, such as emulsifiers, and flavourings, were categorised as UP [16,18]. Information on the coded variables is provided in Appendix A (Table A1).…”
Section: Product Categorizationmentioning
confidence: 99%
See 1 more Smart Citation
“…• National nutrition policy should consider promoting breastfeeding and increasing fresh and minimally processed food consumption in children under 2 years. Rocha et al (2021) evaluated commercial baby food availability and child nutritional status in Natal, Brazil. They found that the food was predominantly ultra-processed (79%); only 4.2% was minimally processed, with similar proportions of ultra-processed food found in high-and low-income areas.…”
Section: Key Messagesmentioning
confidence: 99%
“…Rocha et al ( 2021 ) evaluated commercial baby food availability and child nutritional status in Natal, Brazil. They found that the food was predominantly ultra‐processed (79%); only 4.2% was minimally processed, with similar proportions of ultra‐processed food found in high‐ and low‐income areas.…”
Section: Introductionmentioning
confidence: 99%